2005
DOI: 10.1002/app.22283
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated segmented polyurethane anionomers for water–oil repellent surface treatments of cellulosic substrates

Abstract: Three model structures of linear segmented anionomeric polyurethanes based on perfluoropolyether dimethylol-terminated oligomers, isophorone diisocyanate, and dimethylol propionic acid were synthesized and obtained in the form of aqueous dispersions. The structures differed from each other in the chemical nature of the chain extender (diol or diamine) and in the content of carboxylic acid. Dispersions and polymer films were characterized by dynamic light scattering, dynamic mechanical analysis, differential sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Table presents the values of glass transition ( T g ) temperature at increasing COOH‐CNT concentration. Because of the presence of urethane moieties, the corresponding nanocomposites showed two distinct glass transitions that can be ascribed to the nanoscale segregation of the PFPE phase and the urethane phase resulting from their different solubility parameters . In particular, the lower T g value is related to the soft fluorinated phase ( T g F ), while the higher T g value is associated to the hydrogenated urethane phase ( T g H ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table presents the values of glass transition ( T g ) temperature at increasing COOH‐CNT concentration. Because of the presence of urethane moieties, the corresponding nanocomposites showed two distinct glass transitions that can be ascribed to the nanoscale segregation of the PFPE phase and the urethane phase resulting from their different solubility parameters . In particular, the lower T g value is related to the soft fluorinated phase ( T g F ), while the higher T g value is associated to the hydrogenated urethane phase ( T g H ).…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of the waterborne PFPE‐PUs used in this study is based on a process described elsewhere (see Figure S1 in the Supporting Information for the molecular structure) . Such system is an aqueous dispersion of an anionic segmented PU containing PFPE blocks and carboxylate functional side groups with a solid content of 26% w/w and a molecular weight of about 20,000 g/mol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these products it was observed that water permeability, barrier properties and durability are largely affected by phase segregation phenomena involving the apolar fluoroether segments and polar urethane moieties [2]. More recently waterborne versions of fluoroether containing polyurethanes have been described [5,6]; they are based on the introduction within the polymer chain of ionic groups which act as internal emulsifiers allowing the formation of stable and environmentally friendly aqueous dispersions.…”
Section: Introductionmentioning
confidence: 98%
“…However, the low reaction activity of the fluorinated polyol leads to the low molecular weight and poor mechanical property of the resulting products, which may restrict the wide applications of fluorinated polyurethane (FPU). Moreover, compared to other polyols, the fewer species and quantities of the fluorinated polyol further limited their use as modifying monomers for fluorinated polyurethane [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%